2010
DOI: 10.1007/s10295-010-0718-5
|View full text |Cite|
|
Sign up to set email alerts
|

Photoprotective compounds from marine organisms

Abstract: The substantial loss in the stratospheric ozone layer and consequent increase in solar ultraviolet radiation on the earth's surface have augmented the interest in searching for natural photoprotective compounds in organisms of marine as well as freshwater ecosystems. A number of photoprotective compounds such as mycosporine-like amino acids (MAAs), scytonemin, carotenoids and several other UV-absorbing substances of unknown chemical structure have been identified from different organisms. MAAs form the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
143
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(145 citation statements)
references
References 219 publications
(177 reference statements)
1
143
0
1
Order By: Relevance
“…Additionally, it has been proposed that MAAs are involved in the stress response during drought, as the production of photoprotective compounds such as MAAs, as well as carotenoids and some other UV-absorbing substances, was influenced by environmental stress, including desiccation (74). A study of cyanobacteria showed a positive correlation between MAA synthesis and exposure to drought and irradiation stress (101).…”
Section: Diverse Functions Of Maasmentioning
confidence: 99%
“…Additionally, it has been proposed that MAAs are involved in the stress response during drought, as the production of photoprotective compounds such as MAAs, as well as carotenoids and some other UV-absorbing substances, was influenced by environmental stress, including desiccation (74). A study of cyanobacteria showed a positive correlation between MAA synthesis and exposure to drought and irradiation stress (101).…”
Section: Diverse Functions Of Maasmentioning
confidence: 99%
“…Flavanoids are a class of low molecular weight natural polyphenoic compounds that have the ability to donate a hydrogen atom or an electron in order to form stable radical intermediates, which renders them antioxidant properties (Hajimahmoodi et al, 2010). Their chemical diversity, absorption properties and biotechnological potentials as antioxidant, antibacterial, antioncogenic and antiinflammatory agents are reviewed (Rastogi et al, 2010;Ververdis et al, 2007). The antioxidant activity of hexane fractions of Limnothrix sp and Leptolyngbya sp were confirmed using ABTS decolouration assay, DPPH radical scavenging activity and total antioxidant activity by FRAP assay.…”
Section: Uv Treatment and Ros Assaymentioning
confidence: 99%
“…ycosporine-like amino acids (MAAs) are commonly found in marine microbes exposed to high levels of UV radiation, including aquatic fungi, eukaryotic algae, and cyanobacteria (1)(2)(3)(4)(5)(6). These small (Ͻ400 Da), colorless, water-soluble compounds are composed of a 4-deoxygadusol core conjugated with an amino acid or alcohol (7).…”
mentioning
confidence: 99%